Integrated Analysis Reveals Altered Lipid and Glucose Metabolism and Identifies NOTCH2 as a Biomarker for Parkinson's Disease Related Depression - Dong, Mei-Xue; Feng, Xia; Xu, Xiao-Min; Hu, Ling; Liu, Yang; Jia, Si-Yu; Li, Bo; Chen, Wei; Wei, You-Dong (Frontiers in Molecular Neuroscience, 2018)
Depression is a common comorbidity in Parkinson’s disease (PD) but is underdiagnosed. We aim to investigate altered metabolic pathways of Parkinson’s disease-related depression (PDD) in plasma and identify potential biomarkers for clinical diagnosis. Consecutive PD patients were recruited, clinically assessed and PDD patients identified. Fasting plasma samples were collected from 99 patients and differentially expressed metabolites and proteins between PDD and PD patients identified using non-targeted liquid chromatography-mass spectrometry-based metabolomics and tandem mass tag-based proteomics analysis, followed by integrated analysis. Based on the above results, enzyme-linked immune sorbent assay tests were then performed to identify potential biomarkers for PDD. In clinic, PDD patients suffered less hypertension and had lower serum low-density lipoprotein cholesterol and apolipoprotein B levels compared with the other PD patients. A total of 85 differentially expressed metabolites were identified in metabolomics analysis. These metabolites were mainly lipids and lipid-like molecules, involved in lipid and glucose metabolic pathways. According to proteomics analysis, 17 differentially expressed proteins were identified, and 12 metabolic pathways were enriched, predominantly related to glucose metabolism. Integrated analysis indicated that altered lipid and glucose metabolism in PDD may induce cellular injury through oxidative stress. Additionally, plasma levels of several proteins were confirmed to be significantly altered and correlated with depressive severity. NOTCH2 may be a potential blood biomarker for PDD, with an optimal cut-off point of 0.91 ng/ml, a sensitivity value of 95.65%, and a specificity value of 81.58%. Depressive symptoms are associated with lipid and glucose metabolism in PD patients and NOTCH2 may be a potential blood biomarker for the clinical diagnosis of PDD.